2014
DOI: 10.11646/phytotaxa.164.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Brasilonema roberti-lamii (Cyanophyceae, Nostocales, Scytonemataceae), from Central Mexico

Abstract: This paper is a contribution to the morphological and molecular characterization of the cyanobacterium Brasilonema robertilamii from populations found in Central Mexico. The general growth form and the morphological, morphometric and ecological characteristics of the populations studied clearly correspond to those described for Brasilonema roberti-lamii (basionym: Tolypothrix roberti-lamii) from the French Antilles. Based on molecular data from DNA sequencing of the16S rRNA gene and the IGS of the cpcB-cpcA ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…Our strain did exhibit both “C” and “J” shaped trichomes, similar to our closest relative, B. roberti‐lammi (Rodarte et al. ). While Brasilonema is described as nonattenuated, our new taxon did exhibit rare heteropolarity.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our strain did exhibit both “C” and “J” shaped trichomes, similar to our closest relative, B. roberti‐lammi (Rodarte et al. ). While Brasilonema is described as nonattenuated, our new taxon did exhibit rare heteropolarity.…”
Section: Discussionsupporting
confidence: 80%
“…Several aerophytic, epiphytic, and epilithic Brasilonema species have been isolated from Hawaii, central Mexico, and Brazil (Aguiar et al 2008, Vaccarino and 228 2014). Brasilonema lichenoides was most closely related to B. roberti-lamii, and both strains were growing epilithically in warm humid climates (Rodarte et al 2014). One of the defining features of Brasilonema is the presence of vacuole-like structures (actually free spaces within protoplasts surrounded by thylakoids; Fiore et al 2007), but the new strain did not exhibit such vacuolization in natural populations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…(currently included in Scytonemataceae) by González-Resendiz et al (2015), based on morphological features such as intercalary heterocytes, development of isopolar hormogonia, occasional geminate false branches, and fasciculated filaments. Although, some morphological traits are close to the Brasilonema genus circumscription, distinctive traits such as the peculiar "bead-like" apical cell, heterocyte size and serial disposition, and distribution in supra and intertidal marine biotopes, in contrast to the freshwater and mainly subaerial habitat of typical Brasilonema species (Fiore et al 2007;Santa'anna et al 2011;Vaccarino et al 2012;Rodarte et al 2014), suggested that it belonged to a separate taxon. Even though the environmental populations have morphological traits that differ from typical Rivulariaceae, phylogenetically they clearly belong to this family and are distant from Brasilonema and other members of the Scytonemataceae.…”
Section: Discussionmentioning
confidence: 99%